SISTEM KESANTUNAN SERTA REFLEKSI BUDAYA DARI KOMUNITAS ORANG TUA MURID TIONGHOA SURABAYA DI TBI SURABAYA - Robby Andre (Department of Master of Linguistic, Universitas Airlangga, 2018)
This study examines the prevailing politeness system in the Tionghoa parent community students in TBI (The British Institute) Surabaya and the cultural reflection that can be seen from the use of language in the community. The method that was applied in this research is qualitative method. Sources of data in this study were taken from conversation recordings among the informants. Meanwhile, the theory used in the research was the theory of politeness system formulated by Scollon and Scollon (2001). The results of this study indicated that the system of politeness adopted by the Tionghoa parent community of students in TBI Surabaya was a system of solidarity politeness. In this system of politeness there was no difference in distance and power among members of the community. In addition, the Tionghoa parent community in TBI Surabaya also had a distinctive feature of using the language; there was a mixing of Javanese Ngoko, Indonesian and Hokkien dialect, Mandarin as linguistic markers that distinguished their language use from the indigenous people of Surabaya. Moreover, cultural reflection resulting from the use of mixed language between Javanese Ngoko and Hokkien dialect showed that there is an egalitarian system applied in the community.